Why Not Escape? On the Hosiotes in Plato’s Crito - Komorowska, Joanna (Peitho. Examina Antiqua, 2011)
While the article discusses the factors that motivated Socrates’ decision in the Crito, it emphasizes the possible cultural import of the choice undertaken in the aftermath of the political upheavals in the late fifth century. It is also argued here that as Plato’s dialogue were written in the period that followed the renewal of the Athenian politeia, it should be perceived as having its roots both in the historical reality of its narrative focus (i.e. Socrates’ trial) and in the then reality of Plato’s Athens (i.e., its political stability dependent on the ephebic oath).